PENGEMBANGAN MEDIA SMART CARD BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN IPA TOPIK KERANGKA MANUSIA KELAS VIII SMP - Almajri, Fiqri; Novrianti; Masnur, Alkadri; Masriani, Elsa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research and development (R&D) study aimed to produce a Smart Card learning media based on Augmented Reality (AR) on the Human Skeleton topic for Grade VIII students at SMP Negeri 34 Padang. The development model employed was the 4D model (Define, Design, Develop, Disseminate) proposed by Thiagarajan et al. (1974). The Smart Card integrates text, images, 3D animations, and narrated audio to provide an engaging, student-centered learning experience. Validity assessment was conducted by one subject matter expert (content validity 94.12%, Very Valid) and two media experts (media validity 98.67%, both Very Valid). Practicality testing involving 29 Grade VIII students yielded an overall score of 93.79% (Very Practical). These results demonstrate that the Smart Card based on Augmented Reality developed is both valid and practical for use in science learning, particularly for improving students' understanding of the human skeletal system.